Slovenski kraji spomina. Pojmi, teze in perspektive zgodovinskih raziskav - Jerše, Sašo (Zgodovinski časopis, 2017)
One of the central public discourses in the contemporary European political societies is the memory discourse, whose central message is that without memories of endured suffering it might always return. History, the study of the past, is thereby ascribed an important, even actualistic role: History, the study of the past, becomes in the contemporary memory discourse the narrative about the future for the present, which is is a distinct modern and postmodern phenomenon. Now, each memory discourse consists of cultural and historical cornerstones as well as those associated with the society%s constitution. The French historian Pierre Nora referred to these cultural cornerstones as the realms of memory (les lieux de mémoire). Without an ambition to provide an in-depth scrutiny of all special features of the contemporary Slovene national memory discourse and the Slovene realms of memory themselves, the treatise offers an outline thereof, dividing them into seven sets: (I) symbols, (II) events, (III) sites, (IV) people, (V) creations, (VI) achievements, along with (VII) heritage, traditions, and identities
Keywords: 20./21.st.; 20th/21th century; historical epistemology; historična epistemologija; history; kraji spomina; memory; realms of memory; slovene historiography; slovensko zgodovinopisje; spomin; zgodovina